Prilog poznavanju mobilnosti stanovništva Koprivnice do početka 17. stoljeća - Petrić, Hrvoje (Array, 2003)
According to provided records, we can establish that by 17th century Koprivnica already had relatively numerous communications, not only with surrounding urban settlements, but with more distant regions. Up to now, this topic has been rarely researched. This is why this text here is only a small contribution and an insight into the subject of research. The research covers settlement to Koprivnica area, local students studying at various European universities, migrations due to anti-Ottoman wars and fears from the Ottomans. Additionally, it covers pilgrimage of local inhabitants, but also the other pilgrims visiting Koprivnica and its greater area as well. I also tried to estimate the number of inhabitants of that time, coming to conclusion that most likely population had been growing until the mid-fifteenth century, after that, population was on a continuous decline, reaching its lowest point by the end of sixteenth and in early seventeenth century. This indicates that Koprivnica was faced with its long, major economic and social crisis as early as mid-fifteenth century. This means the immediate cause, after all, was not direct attacks by the Ottomans. Being on the borderline between two great empires - the Hapsburg and the Ottoman - Koprivnica was, in later war activities, both experiencing drawbacks but also the advantages of this position and overall situation. Economic and social life of Koprivnica inhabitants not only suffered, but in a way flourished. All data indicate that a relatively great mobility of people existed, especially late Middle Ages urban and clerical population in Koprivnica. However, we can discuss sixteenth century population of Koprivnica only in terms of currently existing facts and historic comprehension.